Study the features of bone architectonics in sites of subantral augmentation using xenogenic bone graft - Shpacinsky, O.; Skibitskiy, V.; Kopchak, A. (Actual Dentistry, 2018)
Objective: study the features of bone architectonics in sites of subantral augmentation using xenogenic bone graft based on CT scan. Methods. 30 patients with bone deficiency in the distal upper jaw, who had had subantral augmentation using xenogenic bone graft. The bone architectonics was studied by CT, including the evaluation of the bone volume, surface area and density distribution. The obtained data were compared with the normal parameters of the alveolar processes of the upper jaw. Results. Following 6 months after the surgery, the subantral augmentation zone was found to be characterized by a higher density, lack of pores and bone-marrow spaces, a mosaic internal structure with a chaotic alternation of regions of higher and lower radiological density, a simpler geometry of structures with different mineral saturation as compared with the trabecular network of the alveolar process. Conclusions. These differences in the architectonics should be taken into account when installing dental implants and predicting their biomechanical behavior. Key words: sinuslifting, xenogenic material, architectonics, regeneration, remodeling.